Removal of ammonium and manganese from surface water using a MeOx filter system as a pretreatment process - Zhang, Ruifeng (Environmental technology, 2023)
Residual aluminium from the coagulation-sedimentation process in the treatment of surface water can decrease the catalytic activity of a manganese co-oxide filter film (MeOx) used for ammonium and manganese removal. To solve this problem, a MeOx filter was used as a pretreatment process to filtrate source water directly before the coagulation and sedimentation treatment. The removal performance and the mechanism of change in the activity of MeOx were investigated. The experimental results indicated that the MeOx filter removed ammonium and manganese from surface water sources effectively, and its manganese removal activity was enhanced. The characteristics of MeOx were investigated via SEM, EDS, XPS, and the BET surface area. Analysis of the experimental results showed that the increase in the content of Al under this condition was much lower than that under treatment with the coagulation-sedimentation process. After long-term operation, the amount and surface area of MeOx coated on the filter sand increased significantly, leading to an increase in the catalytic activity. However, in cold water, the catalytic activity of MeOx decreased, and more Mn(II) was obtained on the surface of MeOx. Thus, the morphology of MeOx changed. Fortunately, when water temperature increases, the removal activity can recover immediately. By inactivating microorganisms and comparing the removal performance with that under other conditions, the MeOx activity of the pretreatment process is preserved effectively and no strengthening measures are required. This study will provide a new strategy for the use of the MeOx catalytic technology